Compressive Strength and Damage Simulation of Type V Cement-Based Concrete with GGBFS Addition - Audiyati Ishmata Hani'a; Norma Puspita; Marguan Fauzi (Jurnal Teknik Sipil dan Perencanaan, 2025)
The durability of concrete structures in marine environments is often compromised by exposure to aggressive chemical agents. Although Type V cement is designed for high sulphate resistance, it remains susceptible to chloride penetration and magnesium-induced softening. This study investigates the mechanical performance of Type V cement-based concrete modified with GGBFS under simulated marine conditions. Specimens with 0%, 2%, 4%, and 6% GGBFS replacement were cast and cured in synthetic seawater for 7, 14, and 28 days before a compressive strength test. Experimental results showed that 2% GGBFS addition yielded the highest compressive strength of 48.12 MPa, which outperformed the regular concrete (42.32 MPa) at 28 days. Numerical simulations using the Mazars damage model in Cast3M were conducted to complement experimental findings, with mesh densities between 16 and 32 sides. Both experimental and modeling results were compared to BS EN 12390-3:2009 standards to categorize damage patterns. The analysis demonstrated that concrete with 2% dan 4% GGBFS exhibited satisfactory damage behaviour, while 0% and 6% GGBFS mixtures were classified as unsatisfactory. Further, the 16-sided mesh configuration generated damage patterns comparable to 2% and 4% GGBFS specimens, whereas the 32-sided mesh closely aligned with damage characteristics of 0% and 6% GGBFS concrete. This study highlights a novel experimental-numerical framework for optimizing GGBFS levels in marine conditions, demonstrating that integrated approaches effectively enhance performance evaluation and durability assessment.